Measuring the risk and return of Indonesia’s and United States Stock Index - Soegoto, Herman S.; Apsarini, Felicia; Mustapha, Nazar (Journal of Eastern European and Central Asian Research (JEECAR), 2024)
This research investigates the relationship between the returns of selected Indonesian and US stock market indexes and their risks so as to guide new investors on how to choose their investments wisely. A quantitative descriptive method was used using performance data from three Indonesian and three US stock indexes over ten years to calculate an average return. The Sharpe Index was used to measure each index’s risk. The results show that the average stock return for each index in the US is higher than the Indonesia indexes, while the level of risk in the US, on average, is lower. Investors are advised to invest in index categories with higher returns and low risk to increase the chance of gaining better returns while managing their risk to be as low as possible.